Watchdogs : inspectors general and the battle for honest and accountable government - Fine, Glenn A. (Miller Center studies on the presidency., 2024)
"Glenn Fine, who served as the Inspector General for the Department of Justice from 2000 to 2011 and the Acting Inspector General of the Department of Defense from 2016 to 2020, highlights the importance of inspectors general to safeguarding our democracy by drawing on his own experiences in several high-profile investigations during his tenure, from 9/11 through COVID"--